Human Adipose‐Derived Stromal/Stem Cells Protect Against STZ‐Induced Hyperglycemia: Analysis of hASC‐Derived Paracrine Effectors - Kono, Tatsuyoshi M.; Sims, Emily K.; Moss, Dan R.; Yamamoto, Wataru; Ahn, Geonyoung; Diamond, Julie; Tong, Xin; Day, Kathleen H.; Territo, Paul R.; Hanenberg, Helmut; Traktuev, Dmitry O.; March, Keith L.; et al. (Stem cells (Dayton, Ohio), 2014)
Adipose‐derived stromal/stem cells (ASCs) ameliorate hyperglycemia in rodent models of islet transplantation and autoimmune diabetes, yet the precise human ASC (hASC)‐derived factors responsible for these effects remain largely unexplored. Here, we show that systemic administration of hASCs improved glucose tolerance, preserved β cell mass, and increased β cell proliferation in streptozotocin‐treated nonobese diabetic/severe combined immunodeficient mice. Coculture experiments combining mouse or human islets with hASCs demonstrated that islet viability and function were improved by hASCs following prolonged culture or treatment with proinflammatory cytokines. Analysis of hASC‐derived factors revealed vascular endothelial growth factor and tissue inhibitor of metalloproteinase 1 (TIMP‐1) to be highly abundant factors secreted by hASCs. Notably, TIMP‐1 secretion increased in the presence of islet stress from cytokine treatment, while TIMP‐1 blockade was able to abrogate in vitro prosurvival effects of hASCs. Following systemic administration by tail vein injection, hASCs were detected in the pancreas and human TIMP‐1 was increased in the serum of injected mice, while recombinant TIMP‐1 increased viability in INS‐1 cells treated with interleukin‐1beta, interferon‐gamma, and tumor necrosis factor alpha. In aggregate, our data support a model whereby factors secreted by hASCs, such as TIMP‐1, are able to mitigate against β cell death in rodent and in vitro models of type 1 diabetes through a combination of local paracrine as well as systemic effects. Stem Cells 2014;32:1831–1842